Association between maternal anemia and low birth weight among stunting children 12−23 months in Dili, Timor Leste - Florencia Grifit Joiner, Da Costa Hornay; Chandra, Dian Novita; Lestari, Wiji (Indonesian Nutrition Association, 2025)
Background: Stunting is a chronic malnutrition problem primarily occurring during the first 1000 days of life. Iron deficiency anemia during pregnancy can threaten fetal growth and may affect the baby's birth weight and length. According to the Timor-Leste Food and Nutrition Survey 2020, stunting in Timor-Leste is 47.1%. Objectives: To determine the relationship between a history of anemia during the third trimester of pregnancy and low birth weight with the incidence of stunting in children aged 12-23 months in Dili city. Methods: This study was a case-control design conducted in five health centers in Dili City, Timor-Leste. The sample consists of 180 children aged 12-23 months, with 90 stunted cases and 90 controls selected consecutively. Data collected encompasses both child-related and maternal information. Results: Anemia during the third trimester of pregnancy OR 95%CI 7.18 (3.38-15.23) and low birth weight OR 95%CI 5.39 (2.09 – 13.90) are significantly associated with the incidence of stunting (p < 0.01). Based on logistic regression analysis, anemia during pregnancy and low birth weight are not significantly associated with an increased risk of stunting. However, there are characteristics of the mother and child that are significantly associated with the risk of stunting. Conclusion: Children with a history of low birth weight are 5.3 times more likely to experience stunting, and children whose mothers had anemia during pregnancy are 7.2 times more likely to experience stunting. The results show that low birth weight and maternal anemia are related to the incidence of stunting in Timor-Leste.